DESKRIPSI INDUSTRI PENGOLAHAN KELAPA SAWIT - Elan Artono Nurdin; I Gede Sugiyanta; Sugeng Widodo (JPG (Jurnal Penelitian Geografi), 2013)
ABSTRACTThe aim of this research was to find out the plantation of palm oil in PT. Perkebunan Nusantara VII Suni Business Unit at Jemenang village Rambang Dangku sub-district Muara Enim regency South Sumatra in 2012. The focuses of this research were the source of the raw materials, labor, transportation, and marketing.The method used in this research was descriptive method. The subject in this study was the plantation of palm oil in PT. Perkebunan Nusantara VII Suni Business Unit. For data collection, the researcher used observation, interview, questionnaire, and documentation. While data analysis with percentages were used as the basis for the interpretation and description in making of this research report.The results of this research showed that the plantation of palm oil in PT Perkebunan Nusantara VII Suni Business Unit was as following: 1) the origin of raw materials PT. Perkebunan Nusantara VII Suni entirely from farmers who are partners of the company, 2) the work force is working on PT. Perkebunan Nusantara VII Suni comes from within and outside the province of South Sumatra, 3) means of transportation on the PT. Perkebunan Nusantara VII Suni entirely contract status, and 4) the marketing of their products are marketed both in Domestic and Export.Key Word : Industry, Palm Oil